Speech Acts in Classroom Management during Indonesian Language Learning at SMP Negeri 3 Denpasar - I Gusti Ayu Mariyati; Ida Bagus Putrayasa; I Nengah Suandi (GoAcademica Research & Publishing, 2026)
This research aims to describe speech act strategies in classroom management during Indonesian language learning at SMP Negeri 3 Denpasar and the meanings of locution, illocution, and perlocution in classroom management during Indonesian language learning at SMP Negeri 3 Denpasar. The design used in the research is qualitative descriptive. The subjects of the research are teachers and students, and the object of the research is speech acts in classroom management during Indonesian language learning, which includes speech act strategies and the meanings of locutionary, illocutionary, and perlocutionary acts. There are two methods used in the research, namely observation and interview methods. The results of this study indicate that speech act strategies in classroom management during Indonesian language learning include direct literal speech acts and indirect literal speech acts. The meaning of locutionary acts in classroom management, namely commanding, forbidding, or requesting students to perform an action; asking or requesting information; and stating or announcing something; the meaning of illocutionary acts in classroom management, namely ordering, forbidding, urging or directing students; stating information/explanation; giving appreciation/praise; and expressing willingness or commitment; and the meaning of perlocutionary acts in classroom management, namely getting the hearer to do something (making the interlocutor do something). Additionally, there are utterances that have the perlocutionary meaning of bringing the hearer to learn that (making the interlocutor know something), getting the hearer to think about it (making the interlocutor think about something), encouraging, relieving tension, and impressing.